ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI PECAHAN DITINJAU DARI PROSEDUR NEWMAN DI KELAS IV SDN LEBBEK 2 PAMEKASAN - Zaynul Alim, Moh.; Setyawan, Agung; Fadlillah, M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the mistakes made by fourth-grade students at SDN Lebbek 2 Pamekasan in solving story problems on fractions, using the Newman procedure as an analytical framework. The method used in this research is descriptive qualitative, where data is obtained through observation, interviews, and documentation. The research subjects consisted of six students who were selected through purposive sampling based on scores below the Minimum Completeness Criteria. (KKM). This study found that the most dominant student errors occur at the problem transformation stage, where students struggle to determine the correct operational calculations to solve word problems. In addition, there are also errors in understanding the questions and writing the final answers. The factors causing these errors include a lack of understanding of basic mathematical concepts, low skills in performing calculations, and minimal ability to comprehend story problems as a whole. The results of this research provide insights for teachers in improving teaching methods, particularly in fraction material, and help in identifying common mistakes made by students so that appropriate solutions can be provided.